2012
DOI: 10.1007/s13312-012-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio and elevated blood pressure among children in Taiwan

Abstract: WHtR, simple to measure, is an important factor associated with elevated BP in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
8
1
3
Order By: Relevance
“…Thus, it can be inferred that the observed high prevalence may be due to increased central obesity in the studied population. Previous studies reported that increased WHtR strongly predicted the probability of developing hypertension in both children and adults [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be inferred that the observed high prevalence may be due to increased central obesity in the studied population. Previous studies reported that increased WHtR strongly predicted the probability of developing hypertension in both children and adults [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Data from a cross-sectional study among 6–7 year-old children in Taiwan showed that in the combined group of boys and girls, high WC was significantly associated with HBP (aORs were 1.78, 2.45, and 6.03 in the second, third, and fourth quartiles of WC) 41 . A study that included Taiwanese children aged 7 years found that aORs of elevated BP, elevated SBP, and elevated DBP were significant in the second, third, and fourth quartiles of WHtR 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher WHtR ratios were associated with higher MSBP and MDBP in both boys and girls though it was significant in the boys only. Indeed, Chen et al (33) reported an association between higher WHtR ratios and higher MSBP and MDBP in 7 year old boys compared to girls. A recent report by Kruger et al (34) showed that lower WHtR cut-off values (< 41%) are required for the prevention of the metabolic syndrome in black South African adolescents.…”
Section: Correlations Between Msbp/mdbp With Wc Hc and Whtrmentioning
confidence: 99%